Attenuated effect of oxygen on photopigment synthesis in Rhodospirillum centenum. - Yildiz, F H (1991)
Rhodospirillum centenum resembles typical nonsulfur photosynthetic bacteria in a number of respects, including its ability to grow either anaerobically as a phototroph or aerobically as a heterotroph. We demonstrate, however, that R. centenum is unusual in its ability to synthesize a functional photosynthetic apparatus regardless of the presence of molecular oxygen. Aerobically expressed photopigments were shown to be functionally active, as demonstrated by the ability of heterotrophically grown cells to grow photosynthetically, without a lag, when suddenly placed under anaerobic conditions. An R. centenum mutant that has acquired the ability to repress synthesis of photopigments in the presence of oxygen was also characterized. Both the wild type and the oxygen-repressed mutant of R. centenum were found to exhibit high light intensity repression of photopigment biosynthesis. The latter result suggests that R. centenum contains separate regulatory circuits for controlling synthesis of its photochemical apparatus by light intensity and oxygen.